Piligrimage and/or Religious Tourism – Problems and Perspectives of Developement Nowadays - Tonchev, Stefan (Forum Theologicum Sardicense, 2025)
Piligrimage and/or Religious Tourism: Problems and Perspectives of Development Nowadays. This article explores the current issues and prospects for the development of religious tourism in Bulgaria and its theological dimensions in the context of traditional pilgrimage.